Coping with crisis - smoke, drought, flood and currency: Iban women and their households in West Kalimantan - Wadley, R.L. (2002)
In recent years, rural households throughout Indonesia have faced a variety of crises, including severe drought, smoke from forest fires, and floods - all of which have affected subsistence farming. Simultaneous with these problems has been the wider Asian economic crisis that destabilized Indonesia both economically and politically. For rural people, it has affected cash-earning opportunities and prices of basic goods. Focusing on the Iban of West Kalimantan, this paper explores the impacts these various crises have had on Iban farming and wage labor, and how the Iban have coped. It touches on the successful strategies from the past as well as recent local developments that have appeared to cushion the continuing economic uncertainty. This paper contributes to the growing literature on the impact of climatic fluctuation and economic change on the livelihoods of local people in Southeast Asia and other parts of the Third World.